Dietary Factors that Influence Iron Deficiency Anemia in India - Monica Peter; Amrit; Joanne Elizabeth Roshin; Joe Varghese; Padmanaban Venkatesan (Indian Journal of Public Health)
Iron deficiency anemia is a major public health concern in India and is widespread in different regions of this country. Nutritional iron deficiency, in particular, lack of sufficient consumption of heme iron and other dietary factors, are considered to play a role in the high prevalence of anemia in India. In this regard, we constructed a database of nutritional iron consumption by its source and dietary factors that affect iron consumption (Vitamin C, phytates, calcium, and polyphenols) at the district level using the food consumption database extracted from the national household consumption survey. In both rural and urban regions, the consumption of iron from animal sources was only a minor fraction of the total iron consumption. Total and plant sources of iron consumption were comparatively higher in North-Western and Central regions and lower in Eastern regions. Phytates are consumed in higher amounts in many regions of India.